8. EVALUATION OF RESULT OF LAPARASCOPIC GASTRECTOMY FOR TREATMENT OF GASTRIC CANCER AT THE THU DUC CITY HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Object: Evalution the results of laparoscopic gastrectomy + D2 lymph node dissection to treat stomach cancer at the Department of General Surgery, Thu Duc City Hospital from 2019 to 2022.Subject and method: Retrospective, cross-sectional study of gastric cancer cases undergoing radical gastrectomy and D2 lymphadenectomy at Thu Duc City Hospital from January 2019 to October 2022.Result: The mean age of the study group is: 56.8 ± 12.1 years old, the youngest age to get the disease is 35 years old, the oldest age to get the disease is 77 years old. The male/female ratio is: 2.3/1. There were 22 cases (84.6%) with distal gastrectomy and 4 cases (15.4%) with total gastrectomy. The mean surgery time is 239 ± 41 minutes, shortest 130 minutes, longest 340 minutes. There were 10 cases (38.5%) with lesions in the antrum, 10 cases (38.5%) with lesions in the lesser curvature, 1 case (3.8%) in the cardia. The mean size of the lesion is 2.86 ± 1.38 cm, the smallest tumor is 0.8 cm, the largest tumor is 6 cm. The mean number of lymph nodes removed was 15 ± 2 lymph nodes. The mean number of metastatic lymph nodes is 4.7 lymph nodes. There were 10 cases (38.5%) of stage IIIB, 6 cases (23.1%) of stage IIA, 2 cases (7.6%) of stage IA. Regarding differentiation, there were 16 cases (62%) of adenocarcinoma, 6 cases (23%) of poorly differentiated carcinoma, 4 cases (15%) of signet ring cell carcinoma. No cases of complications were recorded after surgery. Hospital stay after surgery: 7.1±1.26 days. We followed up all 24 cases (92.3%). There were 2 cases (7.6%) lost to follow-up. The mean follow-up time is 16 ± 12.9 months, the longest is 45 months, the shortest is 2 months. There were 3 cases (11.5%) of deaths during the follow-up period. The Kaplan Meier estimated mean overall survival was 37.8 ± 3.7 months.Conclusion: Gastrectomy and D2 lymphadenectomy are effective in treating gastric carcinoma
Keywords: Gastric cancer; lasparoscopic; gastrectomy